LOS RECURSOS INFORMÁTICOS EN EL PROCESO DE ENSEÑANZA - APRENDIZAJE DEL ÁREA DE COMUNICACIÓN EN ESTUDIANTES DE EDUCACIÓN INICIAL PISCO PERÚ - Fajardo Cárdenas, Merly Nathaly (2020)
The objective of the research was to determinehow computer resources influence the teachinglearning process in the communication area of thestudents of the III cycle of Initial Education of the HigherPedagogical Institute "Carlos Medrano Vásquez" ofthe district of San Clemente, province of Pisco, 2018.The method used was descriptive hypotheticaldeductive. The design was non-experimental, basicand correlational in scope. We worked with a sampleof 30 students from the initial education specialty ofthe III cycle of the communication area. The data wereobtained through two questionnaires each, whichwere duly validated and reliable for the measurement.The results show a significant influence at 80% of thecoefficient of determination r2 between computerresources and the teaching-learning process in thearea of communication, with a Rho of Spearman of0.826; this relationship being high and significant.(0.000) the use of computer resources influences80% significantly the teaching-learning processes inthe communication area